Outcome Comparison of Single-port Versus Multiport Versus Under Direct View Completion Proctectomy With Ileal-Pouch Anal Anastomosis for Patients With Ulcerative Colitis. Issue 5 (October 2019) - Li, Wanglin; Rencuzogullari, Ahmet; Costedio, Meagan; Benlice, Cigdem; Kessler, Hermann; Stocchi, Luca; Gorgun, Emre
Abstract : Purpose: Whether the reported theoretical benefits of single-port laparoscopic (SPL) approach can be converted to superior clinical outcomes is still unknown for ulcerative colitis (UC) patients undergoing second-stage proctectomy. This study aimed to compare the short-term postoperative and long-term pouch-related functional outcomes of SPL, multiport laparoscopic (MPL), and direct view (DV) completion proctectomy with ileal-pouch anal anastomosis (CP/IPAA). Materials and Methods: Patients who underwent either SPL, MPL, or under DV CP/IPAA for UC between August 2009 and August 2014 were identified from an institutional review board-approved, prospectively maintained institutional database and reviewed. Demographics, patient characteristics, short-term and long-term complications, and morbidity were compared between the 3 groups. Multivariate logistic or Cox regression analysis was conducted for covariate adjustments. Results: Groups (SPL: n=36; MPL: n=67; DV: n=97) were comparable in terms of preoperative characteristics and demographics except for age. The SPL group was associated with reduced estimated blood loss, reduced length of stay compared with the MPL and DV groups, and shorter operating time compared with the MPL group ( P <0.001). Similar short-term postoperative and long-term pouch-related functional outcomes were noted without significant differences in quality of life scores among the 3 groups. Conclusions: SPL CP/IPAA for UC can be safely performed with superior short-term outcomes such as reduced intraoperative blood loss and length of hospital stay compared with MPL and under direct view approaches, and shorter operating time compared with MPL.